2021
DOI: 10.1186/s43044-021-00161-w
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics and outcomes of patients admitted with acute heart failure: insights from a single-center heart failure registry in South India

Abstract: Background The epidemiology of HF in India is largely unexplored. Current resources are based on a few hospital-based and a community-based registry from North India. Thus, we present the data from a single hospital-based registry in South India. Patients admitted with acute heart failure over a period of 1 year were enrolled in the registry and were characterized based on their ejection fraction (EF) measured by echocardiogram. The clinical profile of the patients was assessed, including their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…A single-center HF registry from South India demonstrated T2DM as the most prevalent comorbidity in HFrEF (62.8 %) and HFmrEF (56.6 %) groups compared to the HFpEF group (34.9 %; p < 0.001). 25 Another study from South India reported a much higher prevalence of HFpEF in patients with HF and T2DM (91.2 % versus 43.5 %) compared to patients with HF and without T2DM. 24 The higher proportion of HFmrEF and HFrEF across the HF subgroups in these studies could be due to the inclusion of patients with or without T2DM and HF while we excluded the patients with previously diagnosed HF, CAD, or prior incidence of myocardial infarction.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…A single-center HF registry from South India demonstrated T2DM as the most prevalent comorbidity in HFrEF (62.8 %) and HFmrEF (56.6 %) groups compared to the HFpEF group (34.9 %; p < 0.001). 25 Another study from South India reported a much higher prevalence of HFpEF in patients with HF and T2DM (91.2 % versus 43.5 %) compared to patients with HF and without T2DM. 24 The higher proportion of HFmrEF and HFrEF across the HF subgroups in these studies could be due to the inclusion of patients with or without T2DM and HF while we excluded the patients with previously diagnosed HF, CAD, or prior incidence of myocardial infarction.…”
Section: Discussionmentioning
confidence: 97%
“… 21 Many Indian studies have determined the prevalence of either systolic/diastolic LV dysfunction or HF in patients with and without T2DM 22 , 23 , 24 and assessed the real-world scenario of clinical profile and clinical practice among patients with HF. 25 , 26 However, there is a scarcity of robust large-scale studies evaluating the prevalence of early stages of HF in patients with T2DM, particularly in India. 25 , 27 , 28 Therefore, this registry-based study was conducted to determine the prevalence of LV dysfunction and HF in unselected individuals with T2DM attending outpatient clinics and evaluated their association with comorbidities and other clinical characteristics in India.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Myriads of associated comorbid conditions worsen the prognosis of HF, with associated several million hospitalizations and a major economic burden worldwide. 13 Worldwide, an estimated 64.3 million people have HF. The prevalence of recognized HF is typically considered to be between 1 and 2% of the general adult population in affluent countries.…”
Section: Prevalence: Htn Hfref and Hfpefmentioning
confidence: 99%
“…Comorbidities varied, with coronary artery disease prevalent in 52.5%, type 2 diabetes in 62.8% and 56.6% for HFrEF and HFmrEF, respectively, and hypertension in 48% for HFpEF. Chronic kidney disease was reported in 13% of patients with heart failure [ 7 ].…”
Section: Introductionmentioning
confidence: 99%